What research is needed to validate new urodynamic methods? ICI‐RS2017. (31st July 2018) - Harding, Christopher; Rosier, Peter F.W.M.; Drake, Marcus J.; Valentini, Francoise; Nelson, Pierre P.; Goping, Ing; Gammie, Andrew
Abstract : Aims: In recent years urodynamic innovations, although well researched, have failed to follow a standardized development pathway specifically in terms of clinical trials undertaken to demonstrate efficacy. This was discussed at the International Consultation on Incontinence Research Society (ICI‐RS) in Bristol, United Kingdom, 2017 with the aim of defining minimum standards for future urodynamic research. Methods: The recent recommendations from the IDEAL (innovation, development, exploration, assessment, and long‐term study) collaboration regarding surgical research were reviewed. Two examples of recent novel urodynamic technologies, the penile cuff test and air charged urodynamic catheters were used as case studies and the research programmes behind their development were critiqued. Results: The rigorous and standardized model of surgical research proposed by the IDEAL collaboration was endorsed as an appropriate model for future urodynamic research. A methodical approach to research can fulfil a host of objectives including illustration of the clinical need, help with design and refinement of technique and proving efficacy for any new test or device. The penile cuff test is a novel urodynamic measurement technique that has been well researched and is now used in clinical practice. Further research is needed before air charged catheters can be recommended for widespread clinical use and the IDEAL framework provides a template for ongoing development. Conclusions: In the future, these recommendations should lead to a more standardized and uniform programme of urodynamic research and enable a thorough evaluation of new technologies prior to wider clinical uptake.